Outcome of post-traumatic acute respiratory distress syndrome in young patients requiring extracorporeal membrane oxygenation (ECMO) - Hassan Al-Thani; Ammar Al-Hassani; Ayman El-Menyar; Mohammad Asim; Ibrahim Fawzy (Scientific Reports, 2022)
Abstract We aimed to evaluate the outcomes of post-traumatic acute respiratory distress syndrome (ARDS) in young patients with and without Extracorporeal membrane oxygenation (ECMO) support. A retrospective analysis was conducted for trauma patients who developed ARDS at a level I trauma facility between 2014 and 2020. Data were analyzed and compared between ECMO and non-ECMO group. We identified 85 patients with ARDS (22 patients had ECMO support and 63 matched patients managed by the conventional mechanical ventilation; 1:3 matching ratio). The two groups were comparable for age, sex, injury severity score, abbreviated injury score, shock index, SOFA score, and head injury. Kaplan Meier survival analysis showed that the survival in the ECMO group was initially close to that of the non-ECMO, however, during follow-up, the survival rate was better in the ECMO group, but did not reach statistical significance (Log-rank, p = 0.43 and Tarone-Ware, p = 0.37). Multivariable logistic regression analysis showed that acute kidney injury (AKI) (Odds ratio 13.03; 95% CI 3.17–53.54) and brain edema (Odds ratio 4.80; 95% CI 1.10–21.03) were independent predictors of mortality. Sub-analysis showed that in patients with severe Murray Lung Injury (MLI) scores, non-ECMO group had higher mortality than the ECMO group (100% vs 36.8%, p = 0.004). Although ARDS is uncommon in young trauma patients, it has a high mortality. ECMO therapy was used in a quarter of ARDS cases. AKI and brain edema were the predictors of mortality among ARDS patients. ECMO use did not worsen the outcome in trauma patients; however, the survival was better in those who had severe MLI and ECMO support. Further prospective study is needed to define the appropriate selection criteria for the use of ECMO to optimize the outcomes in trauma patients.